ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK PENERANGAN JALAN TERHADAP PAJAK DAERAH DI KABUPATEN KEPULAUAN TALAUD - Anumpitan, Lonex Dandel; Tinangon, Jantje J.; Runtu, Treesje (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The construction of Talaud Regency encourages the occurrence of increased population, sights, hotels, restaurants and other entertainment venues. Improvement on some of the sectors with increasing power consumption in the Talaud Regency, which would then affect rapidly on increasing tax revenue potential of street lighting. The purpose of this research is to know the tax receipt street lighting in the Department of Revenue , Financial Management and Regional Assets Talaud regency. The results showed that the effectiveness of the tax revenue in the Talaud Regency street lighting from 2011-2015 average of 102.67% – with a good category. While the tax contribution of street lighting towards acceptance of tax areas in the Talaud Regency in 2011-2015 average of 61.22% by category is good enough. This means that the effectiveness of the tax revenue in the Talaud Regency street lighting has been very good and effective tax and contribution to street lighting towards the acceptance of tax areas in the Regency Talaud Regency are already good enough. Keywords : Street Lighting Tax , Effectiveness , Contributions